Potential analysis for patient education in acute non-specific low back pain / Potenzialanalyse zur Patienten/-innenedukation bei akuten unspezifischen lumbalen Rückenschmerzen - Roesner Adrian; Ackenhausen Frauke; Eberhardt Ralf; Gundlach Ulrike; Marquardt Jonas; Voigt-Radloff Sebastian; Schäfer Axel (Sciendo, 2016)
Recent health insurance statistics show that low back pain (LBP) takes the first place in individual diagnoses according to sick leave statistics. As stated by the German back pain study of 2003/2006, long-term prevalence amounts to a total of 74 % to 85 %. In the case of acute unspecific LRS guidelines, recommend the use of non-steroidal anti-inflammatory drugs and patient education in order to motivate the patient to retain an active lifestyle, to stay physically active and to inform the patient about the background of the symptoms. Studies about the current medical supply situation in Germany show injections and passive therapy methods are part of the standard care, whereas educational measures are generally not applied.